A novel sol-gel strategy for constructing wood fibers and aramid nanofiber nanocomposite with strong, tough and recyclable properties. (16th June 2023) - Liu, Tao; Liu, Zheng; Zhou, Zhezhe; Shi, Sheldon Q.; Aladejana, John Tosin; Gong, Shanshan; Fang, Zhen; Li, Jianzhang
Abstract: Recently, biomass-based materials derived from wood processing residues have been developed to resolve the white pollution. However, the poor mechanical strength, weak water resistance, and non-recyclability still limit their practical applications. Aramid nanofiber (ANF) is a promising reinforcement due to the unique structural characteristics and exceptional mechanical properties. Here, a high-performance wood fibers-based nanocomposite was assembled based on chemically-modified wood fiber (CWF) and ANF via a sol-gel strategy with the solvent exchange. The dynamic noncovalent cross-linking with 3D reticular networks between CWF and ANF endow the as-prepared film with high tensile strength of 591.96 ± 11.05 MPa, high toughness of 38.68 ± 2.15 MJ/m 3, and excellent solvent resistance. Moreover, the CWF-ANF gel can effectively repair the fractured CWF-ANF film under heating and maintain competitive mechanical properties after several dissolution-reconstruction, which shows the fascinating sustainability potential. Simultaneously, the as-prepared film is considered as a strong substrate to advance excellently conductive and anti-counterfeiting composite with double-layered structures. This effective strategy provides a novel pathway to reuse plant waste resources with competitive mechanical properties and high value-added utilization. Graphical abstract: Image 1 Highlights: An efficient and low-cost strategy to develop waste wood resources. The conversion process and yield of nature wood powder into nanofibers were studied. A strong, tough, recyclable CWF-ANF nanocomposite is assembled with dynamic noncovalent interactions. The resultant film shows excellently solvent resistance, reparability and recyclability. A novel method of combining natural polymer waste and polymer waste was explored.